Ruminatio philosophiae sebagai strategi formatif imersi spiritual dalam pendidikan agama Kristen - Marbun, Merdiati (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
The phenomenon of spiritual dryness in Christian Religious Education is often caused by an overly cognitive and informative approach, neglecting the formative dimension of students’ inner lives. This study explores ruminatio philosophiae as a formative strategy grounded in philosophical contemplation and Christian spirituality within the learning process of Christian Religious Education. This approach emphasizes deep reflection as a means of holistic faith formation by integrating reason, affection, and action. The study employs a library research method and reflective hermeneutical analysis of both classical and contemporary texts in theology and philosophy. The findings reveal that ruminatio philosophiae is relevant in addressing the crisis of spiritual formation in the context of the digital generation and functions as a pedagogical strategy that cultivates orthodoxy, orthopathē, and orthopraxis. This approach promotes an immersive, reflective, and transformational experience of faith that unites theological knowledge with lived reality. Therefore, ruminatio philosophiae is not merely an educational strategy, but a pedagogical spirituality that revitalizes the praxis of faith education contextually and holistically in Indonesia. Abstrak Fenomena kekeringan spiritual dalam Pendidikan Agama Kristen sering kali disebabkan oleh pendekatan yang terlalu kognitif dan informatif, sehingga mengabaikan dimensi formasi batin peserta didik. Penelitian ini mengeksplorasi ruminatio philosophae sebagai strategi formatif berbasis kontemplasi filosofis dan spiritualitas Kristen dalam pembelajaran Pendidikan Agama Kristen. Pendekatan ini menempatkan refleksi mendalam sebagai sarana pembentukan iman yang menyeluruh dengan mengintegrasikan akal, afeksi, dan tindakan. Penelitian ini menggunakan metode studi pustaka dan analisis hermeneutik reflektif terhadap teks-teks klasik dan kontemporer, baik dari teologi maupun filsafat. Hasil kajian menunjukkan bahwa ruminatio philosophae tidak hanya relevan untuk menjawab krisis formasi spiritual dalam konteks generasi digital, tetapi juga mampu menjadi strategi pedagogis yang membentuk orthodoxy, orthopathē, dan orthopraxis. Pendekatan ini menekankan pengalaman iman yang imersif, reflektif, dan transformasional, yang menyatukan pengetahuan religius dengan kehidupan nyata. Dengan demikian, ruminatio philosophae bukan hanya strategi pendidikan, melainkan spiritualitas pedagogis yang mampu menghidupkan kembali praksis pendidikan iman secara kontekstual dan holistik di Indonesia.